Applied of central composite design for the optimization of removal yield of the ketoprofen (KTP) using electrocoagulation process. Issue 18 (12th December 2019) - Madi-Azegagh, Katia; Yahiaoui, Idris; Boudrahem, Farouk; Aissani-Benissad, Farida; Vial, Christophe; Audonnet, Fabrice; Favier, Lidia
ABSTRACT: In this paper, the modeling and the optimization of the removal efficiency of ketoprofen (KTP) by the electrocoagulation process were studied. The central composite design experiments (CCD) method was used to study the main effects and the interaction effects between operational parameters and to optimize the value of each parameter. According to the regression equation obtained, the current density appears to be one of the most important parameters (b2 = +22.11) controlling the removal efficiency of KTP. The positive sign of b2 coefficient suggests that the increase of current density increases the yield of removal. The second signiﬁcant parameter with a negative effect was the initial KTP concentration (b3 = −16.27). This result suggests that the removal efficiency was inversely proportional to the initial concentration. In addition, according to the model, the most influencing interactions were pH-current density, pH-initial concentration, and current density-initial concentration. The model obtained by CCD led to the following optimal conditions for KTP removal eﬃciency (96.70%): pH = 7, i = 24.04 mA cm −2, and C0 = 5 mg L −1 .